2015
DOI: 10.1002/anie.201411601
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Catalysis: Enantioselective Propargylic Alkylation of Propargylic Alcohols with Enecarbamates Using Ruthenium/Phosphoramide Hybrid Catalysts

Abstract: The diastereo- and enantioselective propargylic alkylation of propargylic alcohols with E-enecarbamates in the presence of a catalytic amount of thiolate-bridged diruthenium complexes bearing an optically active phosphoramide moiety gives the corresponding propargylic alkylated products (up to 97 % ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Nishibayashi and co-workers in the year 2015 have reported a highly diastereo and enantioselective propargylic alkylation of propargylic alcohols 209 with E-ene-carbamates 274 in the presence of a catalytic amount of a thiolate-bridged diruthenium complex, bearing an optically active phosphoramide moiety, Scheme 121. 156 The authors have designed a hybrid catalyst consisting of a thiolate-bridged diruthenium complex tagged with (R)-BINOL based phosphoramide moiety with the rationale that the ruthenium complex will activate the allenediene intermediate and the phosphoramide will guide the ene-carbamate to control the nucleophilic attack, Fig. 19.…”
Section: Scheme 98mentioning
confidence: 99%
See 1 more Smart Citation
“…Nishibayashi and co-workers in the year 2015 have reported a highly diastereo and enantioselective propargylic alkylation of propargylic alcohols 209 with E-ene-carbamates 274 in the presence of a catalytic amount of a thiolate-bridged diruthenium complex, bearing an optically active phosphoramide moiety, Scheme 121. 156 The authors have designed a hybrid catalyst consisting of a thiolate-bridged diruthenium complex tagged with (R)-BINOL based phosphoramide moiety with the rationale that the ruthenium complex will activate the allenediene intermediate and the phosphoramide will guide the ene-carbamate to control the nucleophilic attack, Fig. 19.…”
Section: Scheme 98mentioning
confidence: 99%
“…Nishibayashi and co-workers in the year 2015 have reported a highly diastereo and enantioselective propargylic alkylation of propargylic alcohols 209 with E -ene-carbamates 274 in the presence of a catalytic amount of a thiolate-bridged diruthenium complex, bearing an optically active phosphoramide moiety, Scheme 121 . 156 …”
Section: Different Catalysts Used In Propargylic Substitution Reactionsmentioning
confidence: 99%
“…Recently, Nishibayashi et al disclosed an elegant cooperative dual catalysis using diruthenium complexes bearing a chiral phosphoramide group for enantioselective propargylic alkylations of propargylic alcohols with enecarbamates (Scheme 2). 9 This study suggested the importance of ligand-substrate interactions through hydrogen bonding for high enantioselectivity. 10 3 Scheme 1.…”
Section: Introductionmentioning
confidence: 85%
“…propargylic alkylation of propargylic alcohol with enecarbamate. 9 Herein, we report the synthesis and characterization of a chiral phosphine-phosphoric acid ligand, which possesses both a tertiary phosphine as a metal-coordination site and a BINOL-derived phosphoric acid as a Brønsted acid or an anionic coordination site in the same molecule (Scheme 3). The P,O-chelation properties of the phosphine-phosphoric acid ligands toward rhodium(I) complexes were demonstrated by 4 NMR and single-crystal X-ray diffraction analysis.…”
Section: Scheme 2 Nishibayashi Et Al's Study On the Ruthenium-catalmentioning
confidence: 99%
“…175 Quite recently, Nishibayashi and co-workers reported an elegant diastereo-and enantioselective propargylic alkylation of propargylic alcohols with (E)-enecarbamates through the use of a rationally designed thiolate-bridged diruthenium complex bearing a covalently linked chiral phosphoramide moiety. 176…”
Section: Review Syn Thesismentioning
confidence: 99%